Conceptualising sustainability in the surgical work of non-governmental organisations in low and middle-income countries : a scoping review protocol - Andrew J M Leather; Michelle White; Emma Goettke; Clare Coultas (BMJ Open, 2021)
Introduction Sustainability remains poorly defined in global surgery, yet is, nevertheless, crucial to the work of non-governmental organisations (NGOs) in low- and middle-income countries (LMICs) aimed at strengthening access to, and quality of, surgical and anaesthesia care. The objective of this protocol is to outline a scoping review that maps what is known in the literature about sustainability in NGO surgical work in LMICs.Methods The application of Arksey and O’Malley’s six-stage methodological framework is described: identifying research questions; identifying relevant publications; selecting publications; charting the data; reporting results; and stakeholder consultation. The review will include all study designs, as well as editorials, commentaries, sources of unpublished studies and grey literature. Three electronic databases will be searched. Two reviewers will use predefined and iteratively refined selection criteria based on the ‘Population–Concept–Context’ framework to independently screen titles and abstracts of citations from the search. Disagreements will be resolved together by the reviewers. Full-text screening will also be carried out independently by two reviewers. Disagreements at this stage will be resolved with a third party. The search strategy for grey literature will include searching in ProQuest Dissertations and Theses and the websites listed in a surgical NGO database. Further relevant citations will be identified by screening the reference lists of the included papers.Ethics and dissemination This review will undertake a secondary analysis of data already collected and does not require ethical approval. The results will be disseminated through journals and conferences targeting surgical NGO stakeholders and global health academics.